Communication in graduate management programs: results of a survey - Goodman, M.B.; Hill, J.W.; Greene, K.R. (IEEE transactions on professional communication, 1991)
A study of communication in graduate management programs sponsored by IEEE/PCS and Fairleigh Dickinson University is described. The findings indicate a clear need for more emphasis on oral and written communication and suggest that one solution to the problem is a course requirement in written and oral communication in conjunction with one or two full-time faculty dedicated to the subject. The findings also indicate that full-time faculty who teach communication courses at the graduate level have extensive business and academic experience, and their compensation is well within national guidelines. The study indicates clearly that exit requirements, when they exist, lack both an oral and written communication component, although a written term project for course work is almost universally employed. Other surveys and publications provide background information;.< >